The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fvets.2020.00503
|View full text |Cite
|
Sign up to set email alerts
|

Genome Characterization of mcr-1–Positive Escherichia coli Isolated From Pigs With Postweaning Diarrhea in China

Abstract: Diarrheagenic Escherichia coli is the causative agent of diarrhea in infants and animals worldwide. Many isolated strains recovered from pigs with postweaning diarrhea are multidrug resistance (MDR), and hybrids of E. coli are potentially more virulent, as enterotoxigenic E. coli (ETEC)/Shiga-toxigenic E. coli (STEC) hybrids. Here, we used whole-genome sequencing to analyze clinical isolates of the five colistin-resistant E. coli. The E. coli CAU15104, CAU15134, and CAU16060 belonged to ETEC/STEC hybrids, disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It adheres to the mucosa of the intestines, resulting in acute and persistent watery diarrhea in humans and animals worldwide [2]. EPEC is a major E. coli pathotype that is estimated to be responsible for piglet postweaning diarrhea in China, and a total of 94.15% of 171 E. coli isolates from 56 swine farms were multidrug-resistant [3,4]. A new strategy is necessary for the prevention of pathogen infections since antimicrobial resistance becomes general [5].…”
Section: Introductionmentioning
confidence: 99%
“…It adheres to the mucosa of the intestines, resulting in acute and persistent watery diarrhea in humans and animals worldwide [2]. EPEC is a major E. coli pathotype that is estimated to be responsible for piglet postweaning diarrhea in China, and a total of 94.15% of 171 E. coli isolates from 56 swine farms were multidrug-resistant [3,4]. A new strategy is necessary for the prevention of pathogen infections since antimicrobial resistance becomes general [5].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of prior studies investigating the presence of mcr genes in E. coli isolates from diseased or healthy pigs with defined E. coli pathotypes/VAG-typed E. coli did not test for mcr-6 to mcr-10 (Table S3) [44][45][46][47][48]. Only two out of seven studies investigating for mcr-6 to mcr-10 reported mcr-9-positive E. coli from pigs with diarrhea (Table S3) [49][50][51][52]. The first occurrence and distribution of mcr-1-mcr-10 were reviewed recently [6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported mcr-1-harboring plasmids found in different Inc. types, while IncI2, IncHI2, and IncX4 appear to be the most common carriers of mcr-1 (3,(10)(11)(12). The mobility of mcr-1 is difficult to control because mcr-1-harboring plasmids often carry other antimicrobial resistance (AMR) genes, including those encoding resistance to β-lactams, fluoroquinolones, and tetracyclines (8,13,14). For example, Wang et al reported E. coli strain QE11-421, which was isolated from a sputum sample of a 90-year-old male patient receiving treatment in the ICU, was an mcr-1-positive colistin-resistant isolate that co-harbored the bla KPC-2 gene conferring carbapenem resistance (15).…”
Section: Introductionmentioning
confidence: 99%